28 Reweighing of visual information in individuals with chronic ankle instability: systematic review. (12th October 2015) - Song, K; Burcal, C; Hertel, J; Wikstrom, EA
Abstract : Background: While the exact neurophysiological mechanism of chronic ankle instability (CAI) remains unclear, research suggests that CAI associated balance impairments might be due to an inability to appropriately reweight sensory and/or somatosensory information. Objective: To determine if those with CAI place a greater emphasis on visual information relative to uninjured controls. Design: Systematic review. Setting: Not applicable. Participants: Participants with chronic ankle instability. Assessment of risk factors: We searched PubMed, CINAHL, SPORTDiscus, and Scopus databases from origin to May 2015 using the combination of key words including: postural control, postural stability, single limb stance, single leg stance, single leg balance, single limb balance, time-to-boundary, or TTB. Main outcome measurements: Sample sizes, means and SD of TTB outcomes for each group's EO and EC stance were extracted. Results: Weighted means and SD were calculated and the EC to EO effect size (ES) and 95% confidence interval (CI) for each outcome was generated and compared between groups. The 95% CI of the mediolateral (ML) mean [Control: -1.02 (-1.22 to -0.82), CAI: -1.60 (-1.84 to -1.35)), anteroposterior (AP) mean (Control: -1.31 (-1.51 to -1.10), CAI: -2.16 (-2.42 to  -1.88)), and AP SD (Control: -1.30 (-1.50 to -1.09), CAI: -2.10  (-2.36 to -1.83)] TTB outcomes did not overlap indicating significant differences between two groups. However, the 95% CI for ML TTB SD (Control: -0.77 (-0.97 to -0.58), CAI: -1.11 (-1.33 to -0.88)) did overlap. Conclusions: Those with CAI put more reliance on visual information during single leg stance compared to healthy individuals. This result may indicate that sensory weighting differences may be a potential neurophysiologic mechanism of balance deficits associate with CAI.